2000
DOI: 10.1038/sj.bjp.0703406
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of phencyclidine‐induced effects by a nitric oxide donor

Abstract: 1 Phencyclidine (PCP) is widely used as an animal model of schizophrenia. The aim of this study was to better understand the role of nitric oxide (NO) in the mechanism of action of PCP and to determine whether positive NO modulators may provide a new approach to the treatment of schizophrenia. 2 The eects of the NO donor, sodium nitroprusside (SNP), were studied in PCP-treated rats. Following drug administration, behavioural changes and the expression of c-fos, a metabolic marker of functional pathways in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 72 publications
(67 reference statements)
2
50
0
2
Order By: Relevance
“…The nNOS converts L-arginine to NO, thus increased levels of L-arginine may increase nNOS dysfunctional in schizophrenia. However, the administration of L-arginine does not interfere with PCP-induced behavioral effects nor does it alter PCP-induced cfos expression (Bujas-Bobanovic et al 2000a). But this could be due to NO production not being dependent upon the extracellular substrate (Szabó 1996).…”
Section: Nitric Oxide Sodium Nitroprusside and Schizophreniamentioning
confidence: 98%
“…The nNOS converts L-arginine to NO, thus increased levels of L-arginine may increase nNOS dysfunctional in schizophrenia. However, the administration of L-arginine does not interfere with PCP-induced behavioral effects nor does it alter PCP-induced cfos expression (Bujas-Bobanovic et al 2000a). But this could be due to NO production not being dependent upon the extracellular substrate (Szabó 1996).…”
Section: Nitric Oxide Sodium Nitroprusside and Schizophreniamentioning
confidence: 98%
“…Accordingly, a rapidly increasing body of evidence coming from pharmacological studies in animals argues in favour of this hypothesis. [26][27][28][29][30][31][32][33][34][35] Finally, a landmark study by Akbarian et al, 36,37 followed by further histopathological investigations, 38 argues that nitrinergic neurons are pathologically altered in SCZ.…”
Section: Introductionmentioning
confidence: 99%
“…Bujas-Bobanovic et al 4 described that SNP was able to inhibit the schizophrenia-like behavior and brain c-fos expression in rats induced by PCP, an NMDA receptor antagonist. Also, Issy et al 20 reported that SNP attenuated the schizophrenia-like changes in prepulse inhibition in rats induced by amphetamine, a dopaminergic agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Phencyclidine (PCP) and ketamine are widely used in animal models of schizophrenia, and both drugs act by blocking the action of glutamate on N-methyl-D-aspartate (NMDA) receptors 3,4 . These receptors mediate the production of neuronal nitric oxide (NO) and, therefore, the hypothesis was raised that schizophrenia could be related to decreased levels of NO in the brain.…”
Section: Introductionmentioning
confidence: 99%